2008
DOI: 10.1177/030802260807100806
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the Acquisition of Expertise in Upper Limb Hypertonicity Management

Abstract: Issues in the management of upper limb hypertonicity Hypertonicity can be defined as increased resistance of the limbs to passive movement, which is often associated with neurological conditions such as stroke and cerebral palsy. It results from spasticity (hyperactivity of the stretch reflex) and /or changes in the characteristics of the muscular and connective tissues (Gordon 1990, Levin and Hui-Chan 1993, Umphred 2001). Other performance component impairments of the hand and arm resulting from these conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Second, another means of developing expertise is through professional development (e.g. conferences and workshops) (19,40). Such training helps clinicians to remain current in theory and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, another means of developing expertise is through professional development (e.g. conferences and workshops) (19,40). Such training helps clinicians to remain current in theory and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-nine therapists participated in this study with varying levels of experience, ranging from new graduates to therapists with more than 15 years of experience. Approximately one-third of therapists (38%) had more than five years and 62% had less than five years of experience in this field (40). Based on the work of Rassafiani et al (43), participants made treatment decisions and recorded them as described for Study 1, above.…”
Section: Studymentioning
confidence: 99%
“…They reported that this unique feature of the CAP-M assisted them to work through systematically and document their clinical reasoning process. Recent studies have shown that in the area of upper limb hypertonicity management, clinical reasoning is a complex process which is difficult to learn and expertise does not necessarily increase with length of work experience (Rassafiani 2006, Burgess et al 2008. The findings suggest that the CAP-M would therefore be a useful addition to the current upper limb assessments used by both novice and experienced therapists working with children with cerebral palsy.…”
Section: Usefulness Of the Cap-m For Children With Cerebral Palsymentioning
confidence: 99%
“…Previous research has investigated the development of expertise in hypertonicity practice (Burgess et al, 2008;Kuipers & Grice, 2009;Kuipers & McKenna, 2009;Rassafiani, 2009;Rassafiani et al, 2009). Previously, years of experience has commonly been used to identify clinical experts (Rassafiani, 2009).…”
Section: Introductionmentioning
confidence: 99%